2014
DOI: 10.4103/0974-8237.139211
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of lumbar spondylolysis and lumbar disc herniation with lumbosacral nerve root anomaly

Abstract: Lumbosacral nerve root anomalies are the leading cause of lumbar surgery failures. Although co-occurrence of lumbar spondylolysis and disc herniation is common, it is very rare to observe that a nerve root anomaly accompanies these lesions. A 49-year-old male patient presented with sudden-onset right leg pain. Examinations revealed L5/S1 lumbar spondylolysis and disc herniation. At preoperative period, he was also diagnosed with lumbosacral root anomaly. Following discectomy and root decompression, stabilizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In the latter case, patients with spondylolysis may also show spina bifida occulta, scoliosis, spondylolisthesis, disk herniation, Scheuermann's disease (8,19), or a combination of several other nonskeletal related disorders. In particular, dysplastic spondylolysis with spondylolisthesis was also found, as an accompanying sign, in several patients with autosomal dominant brachydactyly (OMIM ID 113100).…”
mentioning
confidence: 99%
“…In the latter case, patients with spondylolysis may also show spina bifida occulta, scoliosis, spondylolisthesis, disk herniation, Scheuermann's disease (8,19), or a combination of several other nonskeletal related disorders. In particular, dysplastic spondylolysis with spondylolisthesis was also found, as an accompanying sign, in several patients with autosomal dominant brachydactyly (OMIM ID 113100).…”
mentioning
confidence: 99%
“…Incidence ranges from 1.3% found during surgery 4 to 2 to 6.7% detected through imaging methods before surgery 3,9-11 and from 8.5% to 30% during studies of cadavers. 12 Most frequently they are reported to be unilateral, usually at level L5-S1, [1][2][3]5,6 and can be a cause of operative failure. 2,13 Of the 200,000 patients operated on annually for herniated intervertebral disks in the United States, 33% were unsuccessful operations.…”
Section: Introductionmentioning
confidence: 99%
“…1,17 Preoperative and perioperative evaluations should be thorough to prevent nerve injury during surgery. 12,15,18 A summary of previous studies revealed some difficulties in diagnosis. Most of the work on lumbosacral nerve root anomalies involved one patient (case reports) or a small series of patients.…”
Section: Introductionmentioning
confidence: 99%